2009
DOI: 10.1590/s0104-42302009000500017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of children with down syndrome treated in a genetics outpatient service in the southeast of Brazil

Abstract: erika@famerp.br SUMMARY Objective. Considering that studies about the frequencies of phenotypic features of Down syndrome (DS) in the Brazilian population with large ethnic variability are scarce in literature, this study analyzed clinical and demographic characteristics of DS children from the Southeastern region of Brazil. MethOds. Sixty-two DS children with free trisomy 21 were evaluated by physical examination using reference values that considered the children´s gender and age at their presentation. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
2
3
2
1
Order By: Relevance
“…In previous studies, the anomalies which are most common in DS cases were congenital heart defect (CHD), the percentage varied from 44.6, 26, and 56.5%. 7 8 9 In the present study, a high proportion (62%) of DS children presented with cardiac anomalies. This is because our center is a tertiary care facility, and hence, more severe cases are referred for evaluation and management.…”
Section: Discussionsupporting
confidence: 47%
“…In previous studies, the anomalies which are most common in DS cases were congenital heart defect (CHD), the percentage varied from 44.6, 26, and 56.5%. 7 8 9 In the present study, a high proportion (62%) of DS children presented with cardiac anomalies. This is because our center is a tertiary care facility, and hence, more severe cases are referred for evaluation and management.…”
Section: Discussionsupporting
confidence: 47%
“…This result is similar to the study of Azman et al 21 that is, the low set ear was found in 56.1% of the sample. Low set ear is also found in most of the samples in the study of Podder et al, 22 that is as much as 71.8%, while the study of Bartelli 23 revealed that low set ear is only found in 16.1% of samples of down syndrome children. The lower ear portion and rotation cause changes in the tragus position that affects the parallelism of the ala-tragus line with the occlusal plane.…”
Section: Discussionmentioning
confidence: 84%
“…DS is the most common aneuploidy compatible with survival, occurring in 1 out of 691 live births (Centers for Disease Control and Prevention [CDC], 2017). People with DS commonly display intellectual disability, hypotonia, and delayed language and speech development (Mundy et al, 1995; Pavarino Bertelli et al, 2009). The DS brain is characterized by a small cerebellum, reduced neurogenesis, dendritic hypotrophy, and altered neurotransmitter and receptor systems (Das et al, 2013; Stagni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%